***please Show Me Step By Step So I Know Where I W

Anonymous

From: -
Posts: -
Votes: -
***please show me step by step so I know where I went wrong**help me find the derivative: I know I must use the product rule first: y=(2x-5)^4(8x-5)^-3 the answer i got is not the same as in the book (btw, there is nothing on the solutions page on chegg for this...this is like the 4th problem, I've only had this for a few days and no one has answered any of my questions correctly so far...) please help!

 

Answer No.1

LondonSam

From: US
Posts: 18
Votes: 36
Y=(2x-5)^4(8x-5)^-3 y ' = (8 (2x-5)^3 (8x-5)^-3) - (24(8x-5)^-4 2x-5)^4)

Answer No.2

Anonymous

From: -
Posts: -
Votes: -
Y=(2x-5)^4(8x-5)^-3 Let (2x-5)^4 = a (8x-5)^-3 = b from product rule d(ab) = a db + b da ==> y' = (2x-5)^4 d ((8x-5)^-3) + (8x-5)^-3 d((2x-5)^4) = 8 (2x-5)^4 (8x-5)^-4 + 4(8x-5)^-3 (2x-5)^3

Answer No.3

BabyMan4

From: US
Posts: 9
Votes: 18
Y=(2x-5)^4(8x-5)^-3 Let (2x-5)^4 = a (8x-5)^-3 = b from product rule d(ab) = a db + b da ==> y' = (2x-5)^4 d ((8x-5)^-3) + (8x-5)^-3 d((2x-5)^4) = 8 (2x-5)^4 (8x-5)^-4 + 4(8x-5)^-3 (2x-5)^3

Your Comment/Solution

Post As: Anonymous [Change]
Enter